NITROGENOUS FERTILIZATION AFFECTS LEAF CONSUMPTION AND UTILIZATION BY PLUTELLA XYLOSTELLA LINN (LEPIDOPTERA: PLUTTELLIDAE) - G. M. BANSODE,; M. S. PUROHIT, (The Bioscan, 2013)
Food consumption and utilization influence metabolism, enzyme synthesis, nutrient storage and other activities. The nutritional ecology of the Plutella xylostella was studied using nitrogenous fertilized leaves as the source of food. In order to have a detailed picture of food utilization, daily measurement of food ingested, faeces produced and weight gain by larva were recorded. The results revealed that amount of food ingested and consumption index were increased proportionally with the increasing level of N applied to host plants. The amount of food ingested was increased gradually with advancement of age, while consumption of food had decreased with advancement of age. Approximate digestibility, efficiency of conversion of ingested food and efficiency of conversion of digested food increased in younger larvae and declined with the advancement of age.